A HISTORICAL OVERVIEW OF MARKET ABUSE IN THE CONTEX OF TRADING IN SECURITIES - Fruzerova, Oksana (Teisė, 2015)
Article begins with an analysis of market abuse definition. Two main forms of market abuse: insider trading and market manipulation, are being discussed. Subsequently the article analysis historical development of market abuse in different world’s financial markets. The most prominent examples of insider trading and market abuse, that occurred worldwide on financial markets of some European countries, USA, Canada and Japan, are being presented.